The media in Peru - Zeta Quinde, Rosa (2022)
Since the last years, within the media landscape, we've been aware of some very punctual aspects: media manipulation, government intervention, media managers corruption, etc. As well as the relation between media entrepreneurs and media companies as legal person, telecommunication laws, public information access, etc. These trends have generated a positive critical attitude in the public and we believe it should drive all actors in the social communications scene to propose integrated innovations for the future. In order to achieve that goal we need to know the industry's situation. This paper intends to convey a consolidated and up-to-date outlook of Peruvian Media.